Genesis and Development of the Scientific Ideas about the Role of Innovation in the Economic Process - G. A. Shcherbakov (Модернизация, инновация, развитие, 2019)
Purpose: the main purpose of this article is to systematize scientific approaches in the field of innovation research, as well as to identify the leading trends and directions of development of innovation theory.Methods: a wide range of research methods was used during the preparation of the article, in particular: system, logical and conceptual-methodological methods.Results: this article contains a detailed review of the leading scientific approaches to the innovation study formed in the last century. The analysis of these scientific theories is carried out. The periodization of the innovation theory development formed by V.Y. Yakovets in 2004 is also updated and supplemented. The author proposes to conduct the process of development of this theory, including the periodization and chronology of stages, starting from the period of origin of the innovation doctrine to the present day.Conclusions and Relevance: the analysis of the leading concepts and theories suggests that scientific ideas about the role of innovation in the economic process have undergone a significant evolution in the 100-year period of their development. From the technical and technological perception of their role, these scientific ideas have progressed to the present time in the direction of the socio-humanitarian paradigm of innovation.